APPLICATION PECULIARITIES OF THE INTERECTIVE TECHNOLOGIES IN PROFESSIONAL FOREIGN LANGUAGE TRAINING OF FUTURE LAWYERS - Bratkova, Olena I. (Educological discourse, 2016)
The analysis of psychological and educational research sources revealed the nature, objectives, principles,structure, forms and methods of interactive learningin higher school;revealed the peculiarities of application the interactivetechnologiesin professional foreign language training of futurelawyersto professionalinteraction.